Chinese American women's sense of identity is a by-product of othering in a thread of sky. - Nur Ashikin Kamaruddin. (2012)
A Chinese American is discernibly Chinese by ethnicity and American by nationality. The affiliation to two cultures, by birth and by “origin” places the Chinese American in a limbo as they attempt to seek a sense of belonging. The access to a ‘pure’ culture like that of American or Chinese is denied and is hardly accessible due to the Chinese Americans’ status as the perpetual foreigner in both America and China.